Mapping of research related to unmanned surface vehicles (USV) (Research, Society and Development, 2022)
Autonomous vehicles have been used for over 60 years, with the advancement of technology and new approaches, unmanned surface vehicles known as USV (Unmanned Surface Vehichle) were developed. This study aimed to quantitatively map the scientific productions related to unmanned surface vehicles (USV), through scientometric analysis, highlighting articles and review articles in this area of ​​knowledge and demonstrating the number of publications until the year 2021. From collections of data in the Scopus and Web of Science databases, exclusion of duplicate documents and previous analyzes of titles and abstracts were carried out, generating a general study portfolio with 1,190 publications. The result of this mapping showed that the research is focused on technologies for the creation of unmanned surface vehicles (USV) with advanced control and automation resources, and that continue to be developed for the improvement of the equipment, it can also be seen that the production on the subject will continue to grow as it is a relatively new subject with great prospects for the development of new research, methods and applications. Finally, it is expected that this study will help in the mapping of research, especially on topics that are not yet widespread in science, to increase visibility and understanding of research innovations.